Politeness Strategies in Lecturer–Student Interaction: A Sociopragmatic Study in Indonesian Higher Education - Mantasiah Mantasiah (Darul Yasin Al Sys, 2026)
Although politeness strategies have been widely examined in pragmatic studies, research specifically addressing their sociopragmatic function in managing face-threatening acts within lecturer-student interaction in Indonesian higher education remains limited. This study aimed to examine how politeness strategies operate as sociopragmatic resources in managing face-threatening acts (FTAs) in classroom discourse. Using an interactional pragmatic framework, the study employed a qualitative discourse-analytic design based on naturally occurring classroom interactions. Data were collected through audio recordings of nine lecturers across three foreign-language education programmes, namely German, Arabic, and Mandarin Language Education, at one Indonesian university, totaling approximately 450 minutes of classroom discourse. The recordings were transcribed verbatim and analyzed sequentially to identify the realization of politeness strategies in institutional interaction. The findings reveal that lecturers deploy politeness strategies dynamically in response to instructional and institutional demands. Positive politeness predominates in instructional and corrective discourse (42%), bald-on-record strategies appear primarily in regulatory contexts (31%), negative politeness minimizes imposition in evaluative settings (14%), and off-record strategies indirectly regulate student behavior (13%). These patterns reflect sociopragmatic variation shaped by institutional roles, cultural expectations, and norms of appropriateness. The study concludes that politeness functions not only as an interpersonal strategy but also as a mechanism for negotiating institutional authority and relational alignment in classroom discourse. These findings contribute to sociopragmatic and classroom discourse scholarship by extending classical face-management models to institutional and hierarchical interaction in Indonesian higher education.